AnalisisVariasiFonem/N/padaMahasiswa Program StudiBahasa JepangUniversitas Riau semester 1dan 5 - Leli Handayani; Arza Aibonotika; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACT Purpose of this study was to examine the ability of the pronunciation of the phoneme /N/ in Japanese language students of Riau University. Phoneme /N/ produce different sounds, depending on what vowels and consonants accompanying before and after. Data analysis was done by collecting the pronunciation of the phoneme /N/ to serve targeted students and the data analyzed.Based on study results, authors concluded that the pronunciation of the phoneme /N/ influenced by the pronunciation habits and meeting phoneme /N/ with accompanying phoneme. Keywords:Phonemes, Pronunciation Habits